The Relation of Care-Giver Language and Children’s Knowledge Construction: It’s Impact on Literacy Achievement - Siregar, Evy I. (Sukma: Jurnal Pendidikan, 2019)
Literacy is a skill that develops along with the nurtured development of a person. For most school children in Indonesia this is a skill that is rarely encouraged, and yet this is the basic skill, the based foundation for academic growth. This paper looks at literacy development through child language development, its interaction with the carers and his/her environment. This is an attempt to look at the problem of the lack of literacy skills faced by Indonesians children and try to argue its stunted development through child language development, linked to their language development. Subsequently, it also attempt to place this issue through an argument that link this early development with the schooling process at the primary level, and how it might impact children’s literacy development.